An Attempt to Develop Students’ Interest and Learning Outcomes in Economics through a combination learning models - Alfiana, Alfiana (Unversitas Negeri Malang, 2019)
The purpose of this study is to find out (1) how the application of the team games tournament (TGT) learning model with word square games on economic subjects of class X IPA 3 Cross Stone City interest, (2) whether the application of teams games tournament (TGT) learning model with word square games can increase learning interest and learning outcomes of economic subjects in class X IPA 3 Cross Interest in the city of stone. Data was collected by looking at observation sheets, questionnaires, student tests, field notes and reflection. The following are the results of the research: (1) The implementation of the team games tournament (TGT) learning model with word square games applied with excellent titles proved to be an increase from cycle I to cycle II, 69.44% to 87.03%, (2) there was an increase in students' interest in learning before and after the application of the team games tournament (TGT) learning model with word square games, namely from students only interest in being very interested in learning, (3) the average value of students through a cycle final test of 36, 1% to 91.66%.Keywords: Teams Games Tournament Learning Model (TGT), Word Square Learning Model, Interests, Learning Outcomes.